Book Review: the Lifecycle of Structures in Experimental Archaeology – An Object Biography Approach by L. Hurcombe and P. Cunningham - Peter Bye-Jensen (EXARC Journal)
This book is made up of 16 papers that are a collection of results from a European Culture Project (OpenArch) that ran from 2010-2015. It was edited by Linda Hurcombe and Penny Cunningham. This work is dedicated to the late shipwright Brian Cumby, who was deeply involved with making replicas of several prehistoric boats. Accordingly, this book concerns itself with bridging the difficult gap between the present and the past. This is done with experimental archaeology in an attempt to create present replicas of past buildings, boats and associated structures.